Participatory design of digital innovation in agricultural research-for-development: insights from practice - Steinke, Jonathan; Ortíz Crespo, Berta; Etten, Jacob van; Müller, Anna (Elsevier, 2022)
Digital development is becoming mainstream in research-for-development. Applying participatory design methodologies in digital development projects can help develop more user-centered innovation. But these processes require new skills and methods from researchers, and research-for-development project context can create challenges for participatory design. This article presents lessons learned from practical experiences within participatory design projects for digital solutions.